Skull Development, Ossification Pattern, and Adult Shape in the Emerging Lizard Model Organism Pogona vitticeps: A Comparative Analysis With Other Squamates - Ollonen, Joni; Da Silva, Filipe O.; Mahlow, Kristin; Di-Poï, Nicolas (Frontiers in Physiology, 2018)
The rise of the Evo-Devo field and the development of multidisciplinary research tools at various levels of biological organization have led to a growing interest in researching for new non-model organisms. Squamates (lizards and snakes) are particularly important for understanding fundamental questions about the evolution of vertebrates because of their high diversity and evolutionary innovations and adaptations that portrait a striking body plan change that reached its extreme in snakes. Yet, little is known about the intricate connection between phenotype and genotype in squamates, partly due to limited developmental knowledge and incomplete characterization of embryonic development. Surprisingly, squamate models have received limited attention in comparative developmental studies, and only a few species examined so far can be considered as representative and appropriate model organism for mechanistic Evo-Devo studies. Fortunately, the agamid lizard Pogona vitticeps (central bearded dragon) is one of the most popular, domesticated reptile species with both a well-established history in captivity and key advantages for research, thus forming an ideal laboratory model system and justifying his recent use in reptile biology research. We first report here the complete post-oviposition embryonic development for P. vitticeps based on standardized staging systems and external morphological characters previously defined for squamates. Whereas the overall morphological development follows the general trends observed in other squamates, our comparisons indicate major differences in the developmental sequence of several tissues, including early craniofacial characters. Detailed analysis of both embryonic skull development and adult skull shape, using a comparative approach integrating CT-scans and gene expression studies in P. vitticeps as well as comparative embryology and 3D geometric morphometrics in a large dataset of lizards and snakes, highlights the extreme adult skull shape of P. vitticeps and further indicates that heterochrony has played a key role in the early development and ossification of squamate skull bones. Such detailed studies of embryonic character development, craniofacial patterning, and bone formation are essential for the establishment of well-selected squamate species as Evo-Devo model organisms. We expect that P. vitticeps will continue to emerge as a new attractive model organism for understanding developmental and molecular processes underlying tissue formation, morphology, and evolution.